Innovation in family business – theorical and empirical observations for future research (National Administration Journal, 2020)
The study of family businesses is increasingly taking its place into the scientific research of organizations. However, it appears that there are still many gaps to fill in order to create a solid theory about it. The objective of this essay is to conduct a literature review of two major themes that are intertwined i.e. the elements to define the said theory and the innovative posture of the latter as key elements to its development. The aim is to contribute to the review of concepts, ideas and relationships present within literature through a critique of the current understanding possibly leading to future lines of research. For one part, the most important findings indicate the need to consider aspects related with the influence of the family in the business, such as involvement, heterogeneity, identity and familiness in the search for a permanent definition of family business. For the other, it is also necessary to highlight the influence that these elements have on the innovative posture of the business, a crucial aspect for the success of any organization, but little studied in this type of activity.
Keywords: Family business; innovation; innovative posture